Exploration Of The Concept Of Literacy Education In Out-Of-School Education - Nibel, Hendrowanto; Mardiana, Dina; Missesa, Missesa (LPPM Universitas PGRI Sumatera Barat, 2025)
Literacy education should be mandatory in every educational institution, formal and non-formal such as out-of-school education. It is very important to organize various literacy activities in a planned and programmed manner, through activities in the classroom as well as based on school and community culture in the surrounding community. The purpose of this study is to explore the concept of humanist literacy education that can be implemented in out-of-school education at the level of elementary school-age out-of-school education (children's age community). This research is a type of Library Research with a qualitative approach to present a reference library on the implementation of the concept of humanist literacy education in out-of-school education. The results of this literature study can be used as a reference for teachers who implement out-of-school education at the level of elementary school children. The exploration of the concept of humanist literacy education that includes literacy and culture that can be implemented in out-of-school education are: (1) functional level, literacy education at the basic level given to learners to be able to use language to fulfill the needs of daily life, such as reading newspapers/news, daily conversations in the community, manuals or instructions; (2) informational level, literacy education that guides learners to be able to access knowledge with language skills or information about local culture that they need for conversation/spoken communication in local languages and Indonesian; and (3) epistemic level, humanist literacy education that guides learners to be able to express knowledge in the target language (local language, Indonesian, or [suggested] in foreign languages).